STRATEGI KOMUNIKASI HUMAS PEMERINTAHAN BADAN NARKOTIKA NASIONAL (BNN) DALAM MENYEBARKAN INFORMASI P4GN MELALUI MEDIA SOSIAL INSTAGRAM @infobnn_ri - Bayu Rafli Hardian; Slamet Parsono (JIKE: Jurnal Ilmu Komunikasi Efek, 2024)
Badan Narkotika Nasional (BNN) declares war against drugs through various efforts. BNN, as a government agency, has the obligation to disseminate information about Prevention, Eradication, Abuse, and Illicit Trafficking of Narcotics (P4GN) to the public to reduce the number of drug abusers. The purpose of this research is to determine the communication strategy of the government public relations of BNN in disseminating P4GN information through the Instagram social media account @infobnn_ri. This study uses the Communication Strategy Stages theory by Canggara (2014), which includes Establishing the Communicator, Establishing the Target Audience, Composing the Message, Establishing the Communication Media, and Evaluation. The approach used is descriptive qualitative through data collection techniques of interviews, observation, and documentation. The results of this study show that BNN's public relations implement a communication strategy in disseminating P4GN information through the Instagram account @infobnn_ri with several stages starting from appointing the Deputy and BNN work units as Communicators, determining the entire Indonesian public as the target audience for P4GN information content, composing the P4GN information content messages before publication, choosing Instagram as the communication media to disseminate P4GN information content, and conducting program evaluation and management evaluation to assess the success of the P4GN program and the communication strategy that has been implemented.